Pelaksanaan Promosi Pegawai Negeri Sipil Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Kolaka Utara - Hasnia, Hasnia; Bake, Jamal; Abdullah, Akhyar (Universitas Halu Oleo, 2020)
The purpose of this study was to analyze the implementation of employee promotion at the Department of Education and Culture of North Kolaka Regency. The research method used is a qualitative approach with a descriptive approach that will describe in general about the problems studied, namely about the implementation of employee promotions in the Education and Culture office of North Kolaka Regency. Based on the results of the study, it can be concluded that, in general, the implementation of employee promotions at the Education and Culture Office of North Kolaka Regency, the fulfillment of promotion requirements has mostly been implemented well. This can be seen in terms of the quality of education. On the other hand, employee promotion is not carried out on predetermined conditions because there are still many employees who are promoted who have low work experience. Sometimes the employee's discipline to be promoted is not appropriate. Likewise, in terms of promotions based on work performance appraisals, there are still employees who have a low work performance assessment but are included in employee promotions. This means that the implementation of employee promotions is not in accordance with established procedures.